2017
DOI: 10.1097/md.0000000000006367
|View full text |Cite
|
Sign up to set email alerts
|

A case report of pycnodysostosis with atypical femur fracture diagnosed by next-generation sequencing of candidate genes

Abstract: Rationale:Pycnodysostosis is a rare autosomal recessive skeletal dysplasia characterized by short stature, craniofacial dysmorphism, acro-osteolysis, osteosclerosis, and brittle bone with poor healing. Pycnodysostosis results from the deficient activity of cathepsin K, a lysosomal cysteine protease that is encoded by CTSK.Patient concerns:We report a Korean adult patient with pycnodysostosis and atypical femur fracture whose diagnosis was confirmed by next-generation sequencing (NGS) of candidate genes. A 41-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 24 publications
3
19
0
2
Order By: Relevance
“…Compared with commercial pigs, small body size is one of the most visible characteristics of BM, probably as an ecological response called out by the need of relatively large heat dissipation area formed through body volume loss to a long-term warm-temperature environment in low latitudes ( Figure 5B) like other species (Forster et al, 2012;Sheridan and Bickford, 2011). Our analysis identified that the contraction of the LILRA and LILRB subfamilies (from 11 and 4 copies in Duroc to 5 and 2 copies in BM, respectively), belonging to the LILR gene family, which is associated with bone development, can result in pycnodysostosis characterized by osteosclerosis, short stature, clavicular dysplasia, and skull deformities in humans (Song et al, 2017) ( Figure 5C). This may explain why BM has a relatively short body length with only 19-20 thoracic and lumbar vertebras, less than that in commercial pigs (21-23 thoracic and lumbar vertebras in Duroc) and low body height with a dramatically shorter fibula than that in Duroc ( Figure S15; Table S1).…”
Section: Evolutionary Status and Small Body Size Of Bmsupporting
confidence: 59%
“…Compared with commercial pigs, small body size is one of the most visible characteristics of BM, probably as an ecological response called out by the need of relatively large heat dissipation area formed through body volume loss to a long-term warm-temperature environment in low latitudes ( Figure 5B) like other species (Forster et al, 2012;Sheridan and Bickford, 2011). Our analysis identified that the contraction of the LILRA and LILRB subfamilies (from 11 and 4 copies in Duroc to 5 and 2 copies in BM, respectively), belonging to the LILR gene family, which is associated with bone development, can result in pycnodysostosis characterized by osteosclerosis, short stature, clavicular dysplasia, and skull deformities in humans (Song et al, 2017) ( Figure 5C). This may explain why BM has a relatively short body length with only 19-20 thoracic and lumbar vertebras, less than that in commercial pigs (21-23 thoracic and lumbar vertebras in Duroc) and low body height with a dramatically shorter fibula than that in Duroc ( Figure S15; Table S1).…”
Section: Evolutionary Status and Small Body Size Of Bmsupporting
confidence: 59%
“…Pycnodysostosis : Subtrochanteric femoral fractures fulfilling criteria for AFFs have been described in 7 adult cases of pycnodysostosis. In 3 of these cases, pycnodysostosis was unmasked after the femoral fracture . Five cases were bisphosphonate‐naïve, whereas prior bisphosphonate use was unknown in the remaining 2 cases.…”
Section: Resultsmentioning
confidence: 99%
“…While holding some well-known drawbacks, the clinical utility of NGS approaches for MGT is undeniable. Over the last decade, a significant number of teams have developed targeted panels for LSDs, which allowed for the molecular characterization of an even higher number of LSDs patients, ending up several diagnostic odysseys [39,[42][43][44][45][46][47][48][49][50][51] In general, panel design may vary significantly depending on its underlying rationale: for LSDs in particular, some teams have developed small and fast-targeted NGS approaches, which rely on the analysis of a small number of genes selected on the basis of overlapping clinical manifestations [41], while others have gone for more comprehensive approaches and included virtually all known LSD-causing genes [42,45]. Some authors have even went a step further and developed an investigational panel including a large number of genes from the autophagy-lysosomal pathway (ALP), regardless of their known involvement with genetic disease [46,47].…”
Section: Discussionmentioning
confidence: 99%